Projected changes in tropical instability wave activity in the Pacific Ocean under greenhouse warming - Aoyun Xue; Samantha Stevenson; Julien Boucharel; Fei-Fei Jin; Wenjun Zhang; Minyang Wang (Proceedings of the National Academy of Sciences, 2026)
Tropical Instability Waves (TIWs) dominate intraseasonal variability in the tropical Pacific Ocean, strongly impacting climate variability and marine ecosystems. However, their response to greenhouse warming remains uncertain because most current climate models cannot resolve them well. Using a suite of high-resolution climate model simulations capable of representing TIWs, we identify two consistent and distinct mechanisms driving the response of TIWs to CO 2 increases. North of the equator, TIW activity intensifies under higher CO 2 due to enhanced meridional shear of the prevailing zonal currents during boreal fall. Along the equator, TIW activity weakens and shifts slightly westward, driven by a reduced meridional temperature gradient and shoaling of the Equatorial Undercurrent. These changes result in a robust decrease in TIW-driven temperature variability and associated eddy dynamical heating along the equator, underscoring their importance for constraining both the magnitude and spatial pattern of future tropical Pacific warming.